FAKTOR-FAKTOR YANG MEMENGARUHI INDEKS ARTIFICIAL INTELLIGENCE GLOBAL - Yanuar Ichwan Satria Nugroho; Triyani Hendrawati; Kennedy Marthendra; Brian Riski Jayama Simanjuntak (LPPM Universitas Bina Bangsa, 2023)
The Global AI (Artificial Intelligence) Index is a value that aims to measure the progress of artificial intelligence (AI) around the world. Currently, technology is increasingly sophisticated and of course makes humans compete to create technology to make life easier. The purpose of this study is to analyse the effect of human resources, infrastructure, and government policies on the global AI index. The method used to determine the relationship between human resources, infrastructure, and government policies with the global AI index is the multiple linear regression method. From the results of data processing, a linear regression = - 7,54675 + 0,65972 + 0,25096 + 0,07672 . Based on this model, the influence of human resources, infrastructure, and government policies has a significant positive effect on the Global AI Index. The coefficient of determination of the model is 0.8833, in other words, human resources (), infrastructure (), and government policy () are able to explain the value of the global AI index (Y) by 88.33% and the remaining 11.67% is explained by other variables